Effects of Preoperative Enteral Nutrition on Postoperative Recent Nutritional Status in Patients with Siewert II and III Adenocarcinoma of Esophagogastric Junction after Neoadjuvant Chemoradiotherapy. (18th August 2018) - Zhao, Qun; Li, Yong; Yu, Bin; Yang, Peigang; Fan, Liqiao; Tan, Bibo; Tian, Yuan
Abstract: Objective: To study the effects of preoperative enteral nutrition (EN) on postoperative recent nutritional status (PRNS) in patients with Siewert II and III adenocarcinomas of esophagogastric junction (AEG) after neoadjuvant chemoradiotherapy (NCRT). Methods: A total of 66 patients with resectable AEG (Siewert II and III) were randomly divided into two groups. The trial group accepted oral nutrition supplementation (ONS) for 7 days before surgery while the control not. Results: Nutrition indexes were higher in trial group after surgery whereas the opposite was true for the diamine oxidase (DAO) andd -lactate ( P  < 0.05). The rate of malnutrition and nutritional risk became lower in trial group on the 8th day after surgery ( P  < 0.05). Injury levels of intestinal mucosa were more severe among control group. The recent prognosis was better in trial group. For patients with or without nutritional risks at admission, the PRNS and recent prognosis were improved by preoperative EN. Logistic regression analysis suggested that preoperative EN could be an independent protective factor of PRNS. Conclusions: Preoperative EN may improve the PRNS and recent prognosis of patients with Siewert II and III AEG after NCRT.